Diagenesis and evolution of the lower Eocene red-bed sandstone reservoirs in the Dongying Depression, China. (June 2018) - Wang, Jian; Cao, Yingchang; Liu, Keyu; Costanzo, Alessandra; Feely, Martin
Abstract: The diagenetic evolution of the lower Eocene red-bed high-quality reservoirs in the Dongying Depression was systematically investigated through an integrated petrographic, petrophysical, fluid evolution and thermal history analysis. The reservoirs experienced several phases of diagenesis, including compaction, carbonate cementation, gypsum and ankerite cementation, feldspar and carbonate dissolution, quartz overgrowth cementation, and clay-mineral cementation and transformation. An early alkaline diagenetic environment caused significant cementation of calcite and gypsum in the reservoir sandstone units near the sandstone-mudstone contacts. Acidic formation fluids caused widespread dissolution of the feldspar and carbonate cements, leading to synchronous occurrences of primary intergranular pores and acidic dissolution pores. From the middle parts of the reservoir sandstone units to the sandstone-mudstone contacts, dissolution wanes gradually with ferro-carbonate progressively diminishing. Migration of exogenetic thermal fluid along faults may have contributed to the gradual decrease in dissolution and the gradual increase in cementation from the lower part to the upper part of fault blocks. The alternating alkaline and acidic diagenetic environments and the distribution of diagenetic products caused the development of the high-quality red-bed reservoirs in the middle part of the thick-layered sandstone units in the lower part of fault blocks. Because of the spatial and temporal relationships between the diagenetic stages and their products, lithological traps of a diagenetic origin were developed in the red-bed reservoirs. Highlights: A detailed analysis of diagenesis in red-bed reservoirs. Red-bed reservoirs experienced alternating evolution of alkaline and acidic diagenetic environments. Differences of reservoir evolution occur in different positions of red-bed sandstones. Lithological traps of a diagenetic origin developed in the red-bed sandstone reservoirs.